A Systematic Literature Review of the Challenges of Adopting and Implementing IFRS for SMEs in South Africa - Segotso, Tlotlo; Mvunabandi, Jean Damascene; Phesa, Masibulele (International Journal of Economics and Financial Issues, 2024)
The aim of this research was to conduct a systematic review of the existing literature regarding the difficulties associated with the adoption and implementation of International Financial Reporting Standards for Small and Medium-sized Entities (IFRS for SMEs). Additionally, the study sought to propose strategies that could assist with mitigating the complexities relating to IFRS for SMEs adoption and implementation in South Africa. When analysing the related literature, the study employed the Systematic Literature Review (SLR) method and followed the Preferred Reporting Items for Systematic reviews and Meta Analyses (PRISMA) guidelines. According to the inclusion criteria, the literature regarded as relevant related to studies published during 2017–2023. Furthermore, this study adopted the institutional theory due to its relevance in modelling the roles of regulators and SMEs in the adoption and implementation of IFRS for SMEs. The study found that the adoption and implementation of IFRS for SMEs presents several challenges, such as low level of education, costs related to the adoption, political pressures, and training and support by regulatory bodies as well as cultural dimensions. To overcome these obstacles, it is suggested that campaigns be used to raise recognition about the latter, providing extensive educational and regular training for accounting professionals. The study provides an insightful review of the challenges of IFRS for SMEs with specific attention on South Africa, informing the accounting standard setters, policymakers, and professional bodies of the accounting standards.